Seashell waste as new materials for daily use products / Nurul Najeeha Nordin - Nordin, Nurul Najeeha (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
Global designers and scientists are inspired by the availability of radical biomaterials that are unusual materials to replace overconsumption-depleted resources in the development of innovative everyday products. Putting biomaterials such as plants, bacteria, fungi, algae, and other organisms into everyday items helps scientists and designers in solving a variety of problems. Moreover, implementing biophilic elements of design indoors may increase people's sense of connection to the environment and their surroundings. In this project, crushing material from seashells was used as a case study to investigate the use of biomaterials in product design. This research aims to explore and develop the possibility of using seashell waste as new materials for daily use products, aiming to add value to seashell waste produced by other industries. Rising seashell waste in landfills especially has caused much environmental pollution the potential of seashell waste is to construct a new alternative material in product design and reduce and at the same time, add value to seashell waste that is produced by other industries.